Clinical Management Strategies of Cardiologists in Heart Failure with Reduced Ejection Fraction in Türkiye - Kocabas, Umut; Ozcalik, Emre; Kivrak, Tarik; Altin, Cihan; Turk, Ugur Onsel (Kare Publ, 2024)
Objective: Integrating heart failure (HF) guideline recommendations into clinical practice takes time and is often suboptimal in real-life settings. Physician-related factors may be significant barriers to the adoption of these guidelines. This survey aims to assess the current opinions of cardiologists practicing in T & uuml;rkiye regarding the management of heart failure with reduced ejection fraction (HFrEF). Methods: The survey comprised 22 questions and was published on the SurveyMonkey platform. Results: A total of 177 cardiologists (mean age: 39.5 years; 73.3% male) participated in the survey. Of these, 38.7% worked in a training and research hospital, and 10.2% were specialists in HF. The threshold EF value to define HFrEF was <= 40% for 80.1% of the cardiologists. While 52.6% of physicians considered angiotensin receptor-neprilysin inhibitor (ARNi) treatment the most effective medication for HF, 62.7% would initiate HF treatment with an angiotensin-converting enzyme inhibitor (ACEi) instead of ARNi due to reimbursement and cost issues. More than half of the cardiologists (52.3%) stated that adding another class of HF medication is more important than up-titrating those already prescribed. Although 69.5% of the study participants indicated prescribing all four classes of HF medications during the initial hospitalization is feasible, most cardiologists preferred a sequential approach starting with ACEi/ARNi, followed by beta-blockers, mineralocorticoid receptor antagonists (MRAs), and sodium-glucose cotransporter 2 inhibitors (SGLT2i). Conclusion: This survey highlights significant discrepancies between guideline recommendations and the real-life clinical practice of cardiologists in T & uuml;rkiye. These results suggest that there is a need for organized action by healthcare providers to improve the implementation of guideline recommendations.
Türkiye’de Azalmış Ejeksiyon Fraksiyonlu Kalp Yetersizliğinde Kardiyologların Klinik Yönetim Stratejileri
Keywords: Guideline; heart failure; recommendation; treatment